CRIMINAL SANCTIONS IN SERBIA FROM 1945 TO 2019 (Heritage, 2022)
The subject of the paper includes the socio-criminological aspect of the development of criminal sanctions through the periods of state transformation of the Republic of Serbia from 1945 to 2019. The hypothetical assumption that started in the paper was that in the seventy-four-year period of functioning and action of Serbia, traditional criminal sanctions (imprisonment and suspended sentence) dominated and that due to social changes, the introduction of alternative criminal sanctions was delayed. The historical, statistical and comparative methods, as well as the operational method of document content analysis were applied in the research. The most significant finding in the paper is that in the first 32 years, a prison sentence dominated, and in the next 42 years, a suspended sentence. There was no mass application of punishment: suspended sentence with protective supervision, punishment of work in the public interest, fine and other alternative sanctions, which only seemingly satisfied the principle of fairness and proportionality.
Keywords: criminal sanctions, security measures, warning measures, criminal legislation